The impact of spiral arms on the star formation life cycle - Romanelli, Andrea; Chevance, Mélanie; Kruijssen, J. M. Diederik; Ramambason, Lise; Querejeta, Miguel; Boquien, Mederic; Dale, Daniel A.; Brok, Jakob den; Glover, Simon; Grasha, Kathryn; Hughes, Annie; Kim, Jaeyeon; et al. (Astronomy and astrophysics, 2025)
The matter cycle between gas clouds and stars in galaxies plays a crucial role in regulating galaxy evolution through feedback mechanisms. In turn, the local and global galactic environments shape the interstellar medium and provide the initial conditions for star formation, potentially affecting the properties of this small-scale matter cycle. In particular, spiral arms have been proposed to play a pivotal role in the star formation life cycle, by enhancing the gas density and triggering star formation. However, their exact role is still debated. In this study, we investigated the role of spiral arms in the giant molecular cloud evolutionary life cycle and on the star formation process in a sample of 22 nearby spiral galaxies from the PHANGS survey. We measured the cloud lifetime, the feedback timescale, the typical distance between independent regions, and the star formation efficiency in spiral arms and inter-arm regions separately. We find that the distributions of the cloud lifetime as well as the feedback timescale are similar in both environments. This result suggests that spiral arms are unlikely to play a dominant role in triggering star formation. By contrast, the star formation efficiency appears to be slightly higher in inter-arm regions compared to spiral arms.
Online veröffentlicht: 20. Juni 2025
Gesehen am 19.01.2026